Prenatal diagnosis of familial 2p15 microduplication associated with pulmonary artery stenosis, single umbilical artery and left foot postaxial polydactyly on fetal ultrasound - Chih-Ping Chen; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Wayseen Wang (Elsevier, 2021)
Objective: We present prenatal diagnosis of familial 2p15 microduplication associated with pulmonary artery stenosis, single umbilical artery and left foot postaxial polydactyly on fetal ultrasound. Case report: A 34-year-old woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed the karyotype of 46,XX. Prenatal ultrasound examination at 21 weeks of gestation showed pulmonary artery stenosis, single umbilical artery and left foot postaxial polydactyly. Repeat amniocentesis was performed at 22 weeks of gestation and array comparative genomic hybridization (aCGH) analysis on the DNAs extracted from amniocytes revealed the result of arr 2p15 (61, 495, 220-62,885,679) × 3.0 [GRCh37 (hg19)] with a 1.391-Mb 2p15 duplication encompassing seven Online Mendelian Inheritance in Man (OMIM) genes of USP34, XPO1, FAM161A, CCT4, COMMD1, B3GNT2 and TMEM17. aCGH analysis on the DNAs extracted from parental bloods confirmed a familial transmission from a normal carrier mother who had no phenotypic abnormality. A 3270-g female baby was delivered at term with mild pulmonary artery stenosis and left foot postaxial polydactyly. The infant had normal physical and psychomotor development when follow-up at age of one year. Conclusion: Prenatal diagnosis of fetal structural abnormalities should include aCGH analysis in addition to conventional cytogenetic analysis.